UMP UI Ikatan Serumpun program focuses on occupational safety and health sustainability - Wan Norfazilah, Wan Ismail (2023)
DEPOK, INDONESIA, 14 June 2023 - The UMP-UI Ikatan Serumpun programme with the theme 'Hand-in-hand towards a Sustainable Tomorrow,' organized by the Faculty of Science and Industrial Technology (FSTI), Universiti Malaysia Pahang (UMP), and the Faculty of Public Health, Universitas Indonesia (UI), has successfully made an impact on community services in Indonesia.